MATERIAL DESIGN TO IMPROVE STUDENTS’ COMMUNICATIVE COMPETENCE : TEXTBOOK ANALYSIS ON I CAN DO IT English For Senior High School Students Grade XI - Sri Anjani Putra (Universitas Muhammadiyah Surakarta, 2014)
As means of communication, both written and orally, English has a very important role to relate knowledge and technology. As it is the first foreign language in Indonesia, English is not easy to learn, especially for senior high school students. Realizing the importance of English, it is equally important to prepare the teachers who will teach it. In this research, the researcher tries to analyze the tasks on I CAN DO IT English For Senior High School Students Grade XI published by Massmedia. The objectives of the study in this research are: 1) to explain what linguistic competence are reflected in the tasks of I CAN DO IT English For Senior High School Students Grade XI 2. To explain what strategic competence were reflected in the tasks of I CAN DO IT English For Senior High School Students Grade XI, 3) To explain what socio-cultural competence were reflected in the tasks of I CAN DO IT English For Senior High School Students Grade XI ,4) To explain what actional competence were reflected in the tasks of I CAN DO IT English For Senior High School Students Grade XI ,5) To elaborate what discourse competence used in the tasks of I CAN DO IT English For Senior High School Students Grade XI,6) To elaborate what frequency of communicative competence reflected in the tasks of I CAN DO IT English For Senior High School Students Grade XI, 7) To elaborate what dominant of communicative competence are reflected in the tasks of I CAN DO IT English For Senior High School Students Grade XI. The research method used in this research is qualitative descriptive research. In this research, the researcher uses documentation as the data collecting teqnique. After analysing the tasks in the textbook entitled I Can Do It English For Senior High School Students Grade XI published by Massmedia, the writer gets the result that the material designed in the tasks of the textbook are” very good” to develop the learners’ communicative competence because the writer finds the tasks that are supposed to develop the learner’s communicative competence are one hundred and fifty-eight (158) tasks out of two hundred and three (203) tasks in the textbook. It means, there are 77,85% tasks designed in developing the learner’s communicative competences